2015
DOI: 10.1186/s13019-015-0360-4
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of 150 TAVI comparing apical versus femoral approaches

Abstract: BackgroundTranscatheter aortic-valve implantation (TAVI) is a new therapeutic choice for treating aortic stenosis in patients considered high risk for surgery. This blooming therapeutic technique still requires evaluation of medium and long term outcome.MethodWe hereby report our results of the first 150 consecutive patients to receive TAVI implants in our population recruited from July 2009 to March 2013 in a retrospective and monocentric study. We analyzed long term morbidity and mortality criteria. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(25 reference statements)
0
7
0
1
Order By: Relevance
“…The remaining 158 articles underwent full-length review and 141 of these were excluded for failing to meet criteria (113 articles did not report the outcomes of interest and 28 articles were not observational studies or RCTs). Seventeen cohort studies [ 13 28 , 34 ] with 5085 patients were included in the meta-analysis to assess the risk of AKI in patients undergoing TA-TAVR versus TF-TAVR (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 158 articles underwent full-length review and 141 of these were excluded for failing to meet criteria (113 articles did not report the outcomes of interest and 28 articles were not observational studies or RCTs). Seventeen cohort studies [ 13 28 , 34 ] with 5085 patients were included in the meta-analysis to assess the risk of AKI in patients undergoing TA-TAVR versus TF-TAVR (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These studies had a heterogeneous definition of AKI as presented in Table 1 . Most included studies [ 13 22 , 24 28 , 34 ] used standard AKI definitions [modified Risk, Injury, and Failure; and Loss; and End-stage kidney disease (RIFLE) [ 35 ], Acute Kidney Injury Network (AKIN) [ 36 ] or Kidney Disease: Improving Global Outcomes (KDIGO) criteria [ 37 ]]. AKI was diagnosed 48–72 h following/after a TAVR procedure in most included studies and only six studies [ 13 , 15 , 18 , 24 , 27 , 28 ] identified AKI at 7 days following a TAVR procedure as suggested by Valve Academic Research Consortium-2 (VARC-2) consensus [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dalším potenciálním úskalím může být brachiální plexus. U některých nemocných leží brachiální plexus proximálně a v bezprostřední blízkosti mý zásah do myokardu levé komory, proto jej většina autorů považuje za nejvíce invazivní a je spojován s vyšším rizikem komplikací a úmrtí [7,24,25]. Vyšší 30denní a roční mortalita je vysvětlována vyšší rizikovostí nemocných, kteří jsou selektováni pro tento přístup, delší výukovou křivkou a menším počtem nemocných.…”
Section: Hrotový Přístupunclassified